2009
DOI: 10.1515/cclm.2009.218
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter evaluation of the hemolysis index in automated clinical chemistry systems

Abstract: Background: In vitro hemolysis, the prevailing cause of preanalytical error in routine laboratory diagnostics, might influence the reliability of several tests, affect the quality of the total testing process and jeopardize patient safety. Although laboratory instrumentation is now routinely equipped with systems capable of automatically testing and eventually correcting for hemolysis interference, to our knowledge there are no reports that have compared the efficiency of different analytical platforms for ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 11 publications
6
64
0
2
Order By: Relevance
“…Olympus AU640 is equipped with automated system for semiquantitavie detection of lipemic, icteric and hemolyzed samples (LIH index). Lippi et al compared the efficiency of different analyzers including Olympus AU680 to evaluate the hemolyzed samples and found that results were satisfactory [12]. In another study, Simundic et al assessed the comparability of automated spectrophotometric detection by Olympus AU 2700 and visual inspection of hemolyzed samples and showed a comparable rate of detection for hemolyzed samples [13].…”
Section: Discussionmentioning
confidence: 99%
“…Olympus AU640 is equipped with automated system for semiquantitavie detection of lipemic, icteric and hemolyzed samples (LIH index). Lippi et al compared the efficiency of different analyzers including Olympus AU680 to evaluate the hemolyzed samples and found that results were satisfactory [12]. In another study, Simundic et al assessed the comparability of automated spectrophotometric detection by Olympus AU 2700 and visual inspection of hemolyzed samples and showed a comparable rate of detection for hemolyzed samples [13].…”
Section: Discussionmentioning
confidence: 99%
“…Type 1: Registration of procedures could be done by circulation questionnaires, aimed at collecting information on how the laboratories handle different parts of the preanalytical phase, e.g., which criteria are used for sample rejection. Type 2: These schemes are similar to usual analytical EQAS, but the circulated material simulates some kind of preanalytical error (e.g., hemolyzed serum) [74]. Case histories can be distributed together with the EQA samples to elucidate how these samples are dealt with, and how the results are communicated to the physicians.…”
Section: External Quality Assessment Schemes For Preanalytical Phasementioning
confidence: 99%
“…Nowadays, many automated chemistry analyzers are equipped with automated serum indices detection system. Such systems use a semiquantitative spectrophotometric measurement, and grade interfering substances into categories, usually reporting a qualitative or quantitative HI, which is proportional to the concentration of free hemoglobin in serum (34). The HI is then compared with alert values specific for the analyte.…”
Section: Detection and Management Of Hemolytic Specimensmentioning
confidence: 99%
“…Nevertheless, a globally agreed policy to deal with hemolyzed specimens is to always ask for new samples to replace those that are hemolyzed. When these cannot be obtained, it is the responsibility of the laboratory specialist to communicate the problem with the requesting physician and seek a solution that is best for patient care (e.g., suppressing all results affected by in vitro hemolysis) (34,35).…”
Section: Detection and Management Of Hemolytic Specimensmentioning
confidence: 99%